Antin-diabetic cognitive dysfunction effects and underpinning mechanisms of phytogenic bioactive peptides: a review - Liu, Xiaoli; Mao, Shenglian; Yuan, Yuxue; Wang, Zilin; Tian, Yang; Tao, Liang; Dai, Jiahe (Frontiers in Nutrition, 2025)
Diabetic cognitive dysfunction is one of the important comorbidities and complications of diabetes, which is mainly manifested by loss of learning ability and memory, behavioural disorders, and may even develop into dementia. While traditional anti-diabetic medications are effective in improving cognition and memory, long-term use of these medications can be accompanied by undesirable side effects. Therefore, there is an urgent need to find safe and effective alternative therapies. Accumulating evidence suggests that phytogenic bioactive peptides play an important role in the regulation of cognitive dysfunction in diabetes. In this review, we explored the relationship between diabetes mellitus and cognitive dysfunction, and the potential and underlying mechanisms of plant-derived bioactive peptides to improve diabetic cognitive dysfunction. We found that plant-derived active peptides alleviate diabetic cognitive impairment by inhibiting key enzymes (e.g., α-glucosidase, α-amylase) to improve blood glucose levels and increase antioxidant activity, modulate inflammatory mediators, and address intestinal dysbiosis. In conclusion, plant-derived active peptides show strong potential to improve diabetic cognitive impairment.